Strategi Diferensiasi Produk, Citra Merek, Targetting, dan Positioning Pasar Terhadap Keunggulan Kompetitif Minuman Lega di Labuhanbatu (Studi Kasus Konsumen Minuman Lega) - Dani, Ayu Rama; Nasution, Ade Parlaungan; Safri, Hayanuddin (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the product differentiation strategy, brand image, targetting and market positioning of the competitive advantage of Lega drinks in Labuhanbatu, a case study of Lega drink consumers. The population in this study are consumers who buy directly at the Lega Outlet located at Jln. Kihajar Dewantara, Kec. Rantau Selatan, Kab. Labuhanbatu. In this study, using a sample of 80 people. This study used the simple random sampling method, where the penarika was randomized by providing equal opportunities for each member of the population to express their opinion. In simultaneous testing (Test F), it is known that product differentiation, brand image, targetting, and market positioning have a positive and significant effect on competitive advantage. Partially (t test) it is known that product differentiation and brand image have a positive effect on competitive advantage. Meanwhile, targetting and market positioning do not have a positive and significant effect on competitive advantage. Through the determinant coefficient test, the Adjusted R Square value of 0.355 or 35.5 can be obtained. Competitive advantage can be explained by product differences, brand image, targetting, and market position, while the 64.5 side can be explained by other variables not discussed in this study. The feasibility test of the research instrument and descriptive analysis of the characteristics of the respondents used the SPSS (Statistical Package For The Social Science) software Version 22.